Transfusion strategies in non-bleeding critically ill adults: a clinical practice guideline from the European Society of Intensive Care Medicine - Vlaar, A; Oczkowski, S; De Bruin, S; Wijnberge, M; Antonelli, M; Aubron, C; Aries, P; Duranteau, J; Juffermans, N; Meier, J; Murphy, G; Abbasciano, R; et al. (Springer Verlag, 2020)
Objective: To develop evidence-based clinical practice recommendations regarding transfusion practices in non-bleeding, critically ill adults.